Obstacles to private power investments in India - Vishvanath V. Desai (Asian Development Bank Institute (ADBI), 2004)
This paper aims to highlight the critical importance of cost recovery in attracting and sustaining private investment for power development. Based on a brief review of Indian experience, it suggests that in the absence of requisite cost recovery, reform of sector policies and institutions alone, is unlikely to mobilise private investment for power development. The paper also suggests that far more focused attention and efforts than in the past need to be given to achieving adequate cost recovery as well as to implications of failure in achieving it.
Keywords: 330; Elektrizitätswirtschaft; Elektrizitätspolitik; Deregulierung; Privatisierung; Kostendeckung; Indien